2020
DOI: 10.3390/nu12103090
|View full text |Cite
|
Sign up to set email alerts
|

Daily Consumption of Coffee and Eating Bread at Breakfast Time Is Associated with Lower Visceral Adipose Tissue and with Lower Prevalence of Both Visceral Obesity and Metabolic Syndrome in Japanese Populations: A Cross-Sectional Study

Abstract: Background: The study aimed to investigate the association between daily consumption of coffee or green tea, with and without habitual bread consumption for breakfast, and components and prevalence of metabolic syndrome in Japanese populations. Methods: The study population consisted of 3539 participants (1239 males and 2300 females). Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using logistic regression analyses to evaluate the associations of daily coffee and green tea consumption wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Independent studies have indicated that gene–diet interactions may be associated with lower BMI among genetically predisposed individuals who drank 1–3 cups of coffee/day [ 27 ]. Similarly, daily consumption of coffee with bread was associated with lower visceral adipose tissue and lower prevalence of visceral obesity and MetS among Japanese population [ 72 ]. However, high coffee consumption of ≥3 cups/day was positively associated with obesity among Korean women [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Independent studies have indicated that gene–diet interactions may be associated with lower BMI among genetically predisposed individuals who drank 1–3 cups of coffee/day [ 27 ]. Similarly, daily consumption of coffee with bread was associated with lower visceral adipose tissue and lower prevalence of visceral obesity and MetS among Japanese population [ 72 ]. However, high coffee consumption of ≥3 cups/day was positively associated with obesity among Korean women [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between skipping breakfast and metabolic diseases remains a controversial issue, particularly in adults. Previous studies have demonstrated a positive association of not having breakfast with cardiometabolic risk factors, including obesity, hypertension, dyslipidemia, and hyperglycemia resulting from the metabolic syndrome in different countries, including Japan, Iran, and German, with different dietary patterns [ 25 , 26 , 27 , 28 ]. Inconsistent results might be related to no consideration of gender differences in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Nordestgaard et al [ 75 ] conducted a Mendelian randomization study including 93,179 subjects, and showed that the consumption of up to four cups of coffee per day was associated with a lower risk of obesity than non-coffee drinkers. Similarly, Koyama et al [ 76 ] reported that the daily coffee intake was associated with lower levels of visceral obesity and metabolic syndrome in a population of 3539 Japanese. Another clinical study indicated that 30 obese women who consumed 180 mg of CGA for eight weeks presented significant reductions in body weight, BMI, and fat mass indices as well as lower serum LDL, TC, leptin, and plasma free FA levels when compared with 34 obese women from the placebo group [ 77 ].…”
Section: Polyphenol Effect On Obesitymentioning
confidence: 96%